Analysis of Frequency Spectrum in Digital Image Transmission Using Orthogonal Frequency Multiplexing - Sarjana Sarjana; Ade Silvia Handayani; Devi Wahyuni (Komunitas Dosen Indonesia, 2025)
Accurate and efficient data transmission is increasingly essential due to the growing reliance on digital communication, particularly for multimedia content such as images. Orthogonal Frequency Division Multiplexing (OFDM) provides high bandwidth efficiency and strong noise resilience by transmitting data over multiple orthogonal subcarriers. Despite its advantages, limited studies have explored how modulation schemes influence frequency-domain characteristics during image transmission under different noise conditions. This study addresses that gap by evaluating digital image transmission through OFDM using Binary Phase Shift Keying (BPSK) and Quadrature Phase Shift Keying (QPSK) modulation. The objective is to compare spectral performance across various signal-to-noise ratio (SNR) levels. A grayscale image is converted into a binary stream, modulated using BPSK and QPSK, and processed through an OFDM system with 512 subcarriers and a 25% cyclic prefix. The signals are transmitted through an Additive White Gaussian Noise (AWGN) channel at SNR values of 0 dB, 5 dB, and 10 dB. Power Spectral Density (PSD) is measured using the Welch method with a Hamming window, 50% overlap, and 1024-point Fast Fourier Transform (FFT). The results show that increasing SNR improves spectral sharpness, reduces the noise floor, and enhances symmetry. BPSK offers better performance in noisy conditions, while QPSK is more efficient in high-SNR environments. These findings provide practical insight for optimizing modulation choices in OFDM-based image transmission systems where spectral efficiency and noise robustness must be balanced.